Age-stratified selection of albumin-based inflammatory ratios: a novel strategy for optimizing risk prediction of severe pneumonia in children - Bai, Yunbao; Zhang, Jianming; Hou, Changxu (Frontiers in Pediatrics, 2025)
BackgroundThis study aimed to optimize risk prediction of severe community-acquired pneumonia (CAP) in children through age-stratified selection of albumin-based inflammatory ratios.MethodsThis retrospective study analyzed 1,071 pediatric CAP patients (aged 1–12 years). Propensity score matching (1:2 severe-to-mild ratio) within three age strata (1–3 years, 4–6 years, 7–12 years) generated balanced cohorts (N = 360). Neutrophil percentage-to-albumin ratio (NPAR), C-reactive protein-to-albumin ratio (CAR), and CRP × lymphocyte-to-albumin ratio (CALLY) were evaluated using multivariate logistic regression and ROC analysis.ResultsSevere CAP incidence increased with age (1–3 years: 7.37%; 4–6 years: 12.80%; 7–12 years: 18.04%). Multivariate analysis identified NPAR as the sole independent predictor for younger children (1–3 years: OR = 10.289; 4–6 years: OR = 35.117), while CAR predicted severe CAP in older children (7–12 years: OR = 3.342). ROC analysis demonstrated robust performance for NPAR in 1–6 years (AUC: 0.748–0.807, NPV: 85.9–88.0%) and CAR in 7–12 years (AUC: 0.734, NPV: 83.0%).ConclusionsNPAR (for ages 1–6 years) and CAR (for ages 7–12 years) serve as effective, age-specific biomarkers for severe CAP, facilitating precise risk stratification with high negative predictive value.